SUPERVISI KLINIS KEPALA SEKOLAH DALAM PENINGKATAN MUTU PROGRAM TAHFIDZ DI MADRASAH TSANAWIYAH PERGURUAN MU’ALLIMAT - Tsania Ittaqi Tafuzi; Muhammad Al-Fatih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of improving the quality of Islamic education through systematic and sustainable professional teacher development. One relevant approach is the principal’s clinical supervision, a guidance process emphasizing partnership, direct observation, reflective dialogue, and feedback based on learning data. In the Qur’an memorization (tahfidz) program, clinical supervision plays an important role in maintaining the quality of learning in accordance with the standards and objectives of Islamic education. MTs Perguruan Mu’allimat, as a pesantren-based Islamic school, has an excellent tahfidz program that requires professional guidance to maintain and improve its quality. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, while data analysis involved data reduction, data presentation, and conclusion drawing. Data validity was tested through source and technique triangulation. The results of the study indicate that: (1) clinical supervision is implemented systematically through preliminary meetings, observation of tahfidz learning, and dialogic feedback; (2) the quality of the tahfidz program is reflected in the improvement of students’ memorization quality, accuracy of tajwid application, discipline in muraja’ah (revision), and the development of Qur’anic character; (3) clinical supervision contributes to improving program quality through teacher development, continuous evaluation, and the creation of a religious and conducive learning environment. Therefore, clinical supervision serves as an effective strategy in maintaining the sustainable quality of the tahfidz program.